Invasive Candidiasis Coinfection in Patients with Severe COVID-19 Disease: Scoping Review - Omar Esteban Valencia-Ledezma; María del Rocío Reyes-Montes; Gustavo Acosta-Altamirano; María Guadalupe Frías-De-León; Eduardo García-Salazar; Esperanza Duarte-Escalante; Jesús Santiago-Abundio; Zuleyma González-Miguel; María de Lourdes García-Hernández; Rebeca Martínez-Quezada; Oscar Uriel Torres-Páez; Evelyn Galindo-Oseguera; et al. (Pathogens)
Coinfection rates of candidiasis in patients affected by COVID-19 had a significantly increase during the sanitary contingency. The objective of this scoping review is to analyze the available scientific evidence around the coinfection of invasive candidiasis in hospitalized patients with severe COVID-19 disease. Online databases such as PubMed, EBSCO, SciFinder, Scopus, and SciELO were used to analyze the different scientific studies published from January 2020 to December 2022, selecting 48 publications that reported comorbidity between invasive candidiasis and COVID-19 as a study variable. Based on the PRISMA-ScR extension for scoping reviews, we identified more than half of the publications (57%) as observational, descriptive, and analytic studies, while 43% were systematic reviews. Overall, up to 169,468 adult patients admitted to the intensive care unit were examined. Coinfection was due mainly to Candida albicans (75%), but some more species were reported such as Meyerozyma parapsilosis (formerly Candida parapsilosis); Meyerozyma guilliermondii (formerly Candida guilliermondii); Nakaseomyces glabratus (formerly Candida glabrata); Candida tropicalis; Candida dubliniensis; Clavispora lusitaniae (formerly Candida lusitaniae); and Pichia kudriavzevii (formerly Candida krusei). We concluded that patients infected by SARS-CoV-2 had a higher incidence of fungal coinfections, thus increasing the mortality rate, disease severity, and length of hospital stay in the intensive care unit.